Comparison of the observed size-dependent melting point of CdSe nanocrystals to theoretical predictions - Dukes III, Albert Demaine; Pitts, Christopher Dylan; Kapingidza, Anyway Brenda; Gardner, David Eric; Layland, Ralph Charles (European Journal of Chemistry, 2018)
Cadmium selenide nanocrystals were observed to have a size-dependent melting point which was depressed relative to the bulk melting temperature. The observed size-dependent melting point ranged from 500-1478 K, while a model based on the surface area to volume ratio predicted that is should range between 774-1250 K. The nanocrystals were heated in situ in the electron microscope, and the melting point was almost immediately followed by the vaporization of the CdSe nanocrystals, allowing for straightforward determination of the melting temperature. The differences between the observed melting point of CdSe nanocrystals and the values predicted by the surface area to volume ratio model indicates that additional factors are involved in the melting point depression of nanocrystals.